Considerazioni sul controtransfert nell’attività clinica basata sulla teoria della nascita - Homberg, Annelore (Il sogno della farfalla, 2015)
This article, which follows on from articles which appeared in the last issues, presupposes that the capacity to know the human mind is a core element in psychic health and that the main aim of therapeutic work is enable patients to realize this capacity. The article begins by considering the attempts made by some psychotherapeutic schools of thought, including classic psychoanalysis, to create an objective knowledge of psychic dynamics. In other psychoanalytic trends the therapist’s subjectivity is at least ancillary in reaching this knowledge and a knowledge based on an “identification” or “empathy” with the patient is proposed. After taking a critical look at such concepts, the Author focuses on the concept of “generic sensibility” arising from the Birth Theory. The article then goes on to analyze countertransference according to the Birth Theory, in particular as featured in M. Fagioli’s Istinto di morte e conoscenza (1972) where countertransference is defined as a global relationship the therapist establishes with his patient who has in turn carried out a transference. Particular importance is given to the concept of negative transference, which in clinical practice based on the Birth Theory is considered an inevitable and central part of a patient’s treatment. The article views countertransference as an expression of the therapist’s psychic attitude which highlights, in addition to a significant degree of psychic well-being, the capacity to embrace a positive transference and frustrate a negative one. Possible countertransference errors are viewed as the “absence of the therapist”. Moreover, a distinction is made between countertransference and a generic diagnostic capacity that arises from the psychiatrist’s subjective sensibility such as, for example, in Praecoxgefühl. The article ends with an examination of the concept of “knowledge through intuition” which the book Istinto di morte e conoscenza explores in depth.